Mind wandering is not always harmful in sports: the role of its content - Li, Jieling; Li, Chuangye; Xue, Shuangpeng; He, Yuxiu (Frontiers in Psychology, 2024)
Objective: Mind wandering (MW) among athletes during training and competition will evidently lead to abnormal performance. However, MW has also been found to have positive effects. This study aims to clarify the cause of bidirectional (negative and positive) effects of MW in the sport context. In particular, whether it is related to MW content. Methods: A total of 846 Chinese athletes completed the Chinese version of MW scales. The survey data were tested for common method biases. Then, Pearson correlation analysis and structural equation modeling were performed by using SPSS 25.0 and Mplus 7.0. Results: The frequency of MW can positively predict its bidirectional effects. MW content plays an important role between MW frequency and negative and positive effects, but the direction of influence varies with different contents. Conclusion: MW in sports is not always harmful, and its content plays an important role. These findings suggest that managing MW content may be a promising MW intervention method for improving performance in sports.